Interdisciplinary challenges and aims of flap or graft reconstruction surgery of sinonasal cancers: What radiologists and radiation oncologists need to know - Carsuzaa, Florent; Verillaud, Benjamin; Marcy, Pierre-Yves; Herman, Philippe; Dufour, Xavier; Favier, Valentin; Thariat, Juliette (Frontiers in Oncology, 2022)
In sinonasal cancer surgery, a fundamental challenge is to understand the postoperative imaging changes after reconstruction. Misinterpretation of post-operative imaging may lead to a misdiagnosis of tumor recurrence. Because radiotherapy planning is based on imaging, there are many gaps in knowledge to be filled in the interpretation of postoperative imaging to properly define radiotherapy tumor volumes in the presence of flaps. On the other hand, radiotherapy may be responsible for tissue fibrosis or atrophy, the anatomy of the reconstructed region and the functional outcomes may change after radiotherapy compared to surgery alone. This narrative review illustrates the interdisciplinary aims and challenges of sinonasal reconstructive surgery using flaps or grafts. It is particularly relevant to radiologists and radiation oncologists, at a time when intensity modulated radiotherapy and proton therapy have the potential to further contribute to reduction of morbidity.